2021
DOI: 10.1097/fm9.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Labor, a Syndrome Attributed to the Combination of External and Internal Factors

Abstract: Preterm labor (before 37 weeks' gestation) is the leading cause of neonatal mortality and morbidity, which can be divided into iatrogenic preterm labor, infectious preterm labor, and spontaneous preterm labor (sPTL). Up to now, there continue to be great difficulties in prediction and prevention of sPTL, owing to multiple risk factors, pathogenesis, and pathologic processes contributing to the event, which have not been fully clarified. Pregnancy maintenance and parturition is a complicated process with contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…We also did not propose a specific mechanism for HIF-1a regulation of TREK1. Mammalian microRNAs (miRNA/miR) play especially powerful roles in smooth muscle cells (55). Hypoxia induces further downregulation of miR-124 (56), and Bucharest et al (57) revealed an inverse correlation between miR-124 and TREK1 expression in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not propose a specific mechanism for HIF-1a regulation of TREK1. Mammalian microRNAs (miRNA/miR) play especially powerful roles in smooth muscle cells (55). Hypoxia induces further downregulation of miR-124 (56), and Bucharest et al (57) revealed an inverse correlation between miR-124 and TREK1 expression in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although some methods show promise, they have not been implemented on a large scale. 7 Recent advances in high-throughput technologies have led to the use of the transcriptome as an effective tool for predicting health outcomes. 8 Transcriptomic signatures change in response to altered pathological conditions in vivo; the identification and assessment of these signatures may therefore help determine the biological status of various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various novel methods for PTB prediction have been studied in recent years; these include the assessment of genetic loci, circulatory protein biomarkers, the vaginal microbiome, and placental elasticity, among others. Although some methods show promise, they have not been implemented on a large scale 7 …”
Section: Introductionmentioning
confidence: 99%